Pengaruh Sense of Humor dan Religiusitas Terhadap Kebahagiaan pada Lansia - Aulia, Ananda Rachma; Adriani, Yufi (‎‎‎TAZKIYA: Journal of Psychology, 2020)
Happiness is what everyone wants. With happiness, individuals can feel various positive effects in influencing every aspect of life. This study aims to prove the effect of sense of humor, religiosity and demographic factors on elderly’s happiness. The subject in this study were 211 elderly aged 60 years or above in DKI Jakarta. The sampling method used non-probability sampling. The instrument used were adapted and modified The Happiness Scale Interval Study (HSIS) (Kalmijn et al., 2011), Multidimensional Sense of humor Scale (MSHS) (Thorson & Powell, 1993), and The Centrality of Religiosity Scale (CRS)(Huber & Huber, 2012). Test the validity of measuring instruments using the Confirmatory Factor Analysis (CFA) technique and hypotesis was tested using multiple regression analysis. This results showed that there was a significant effect of sense of humor, religiosity, and demographic factors on elderly’s happiness with contribution of 36.3%, while the remaining 63.4% were variables outside of this study.